2013
DOI: 10.1371/journal.pone.0058522
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Visitors: Long-Term Behavioural Response of Bull Sharks to Food Provisioning in Fiji

Abstract: Shark-based tourism that uses bait to reliably attract certain species to specific sites so that divers can view them is a growing industry globally, but remains a controversial issue. We evaluate multi-year (2004–2011) underwater visual (n = 48 individuals) and acoustic tracking data (n = 82 transmitters; array of up to 16 receivers) of bull sharks Carcharhinus leucas from a long-term shark feeding site at the Shark Reef Marine Reserve and reefs along the Beqa Channel on the southern coast of Viti Levu, Fiji.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 42 publications
10
70
1
Order By: Relevance
“…As such, the potentially large number of individuals that occur on the GBR likely have a key role as large predators in coral reef environments. Studies of C. leucas in reef habitats in Fiji (Brunnschweiler and Barnett, 2013) would also support the theory that this species is a significant predator in coral reef environments. Thus, adult C. leucas would fit the definition of process links defined by Lundberg and Moberg (2003).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As such, the potentially large number of individuals that occur on the GBR likely have a key role as large predators in coral reef environments. Studies of C. leucas in reef habitats in Fiji (Brunnschweiler and Barnett, 2013) would also support the theory that this species is a significant predator in coral reef environments. Thus, adult C. leucas would fit the definition of process links defined by Lundberg and Moberg (2003).…”
Section: Discussionmentioning
confidence: 80%
“…Recent research has indicated segregation by size may occur in C. leucas populations with smallest individuals using river habitats and largest individuals inhabiting marine regions (Simpfendorfer et al, 2005;Brunnschweiler and Barnett, 2013). Movements and habitat use by juvenile bull sharks has been well-documented in several studies (Heupel and Simpfendorfer, 2008;Heithaus et al, 2009;Heupel et al, 2010;Curtis et al, 2013), but data on adult movements are limited (Daly et al, 2014).…”
Section: Marine Sciencementioning
confidence: 99%
“…If these activities attract whitetips to CI, this intentional and unintentional provisioning of whitetips could impact their life history. In sharks, changes in feeding behavior, aggression, and movement patterns have been suggested and/or demonstrated as a result of provisioning (Fitzpatrick et al 2011, Maljkovi & Côté 2011, Bruce & Bradford 2013, Brunnschweiler & Barnett 2013. Modification of migratory patterns in response to provisioning has been demonstrated in other shark species (Bruce & Bradford 2013), as has a lack of response to provisioning (Hammerschlag et al 2012).…”
Section: Potential Effects Of Provisioningmentioning
confidence: 99%
“…Pierce et al 2010) and been used to formulate and/or improve management strategies to mitigate disturbances (e.g. Bruce et al 2005, Dans et al 2012. Behavioural studies have largely focused on terrestrial vertebrates, particularly birds and mam mals (Bonnet et al 2002, Jennions & Møller 2003, Ord et al 2005, and have extended to the marine environment with cetacean research dominant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Quiros 2007, Cubero-Pardo et al 2011) and abnormal/stereotypic displays associated with provisioning tourism (e.g. Laroche et al 2007, Miller et al 2011, Brunnschweiler & Barnett 2013 for various species.…”
Section: Introductionmentioning
confidence: 99%